English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x-2y+z=9
3x-4y+z=17
2x-y+2z=15

x+y+z=10
2x+y-2z=1
x-y+3z=2

2007-04-27 11:55:32 · 2 answers · asked by Chunky 1 in Science & Mathematics Mathematics

2 answers

x - 2y + z = 9
3x - 4y + z = 17
2x - y + 2z = 15
2x - 4y + 2z = 18
- 3y = 3
y = - 1
2x - 2y = 8
x = 3
z = 9 - 3 - 2
z = 4

6 + 1 + 8 = 15

x + y + z = 10
2x + y - 2z = 1
x - y + 3z = 2
x - 3z = - 9
x + z = 3
-2z = -6
z = 3
x = 0
0 + y + 3 = 10
y = 7

0 - 7 + 9 = 2

2007-04-27 12:30:16 · answer #1 · answered by Helmut 7 · 0 0

on the first one:
(3, -1, 4)

on the second one:
(0, 7, 3)

2007-04-27 12:07:21 · answer #2 · answered by BlondE 25 2 · 0 0

fedest.com, questions and answers